A new method to treat persistent corneal erosions after high-risk keratoplasty - E. V. Chentsova; N. V. Borovkova; D. A. Bozhenko; I. N. Ponomarev; P. V. Makarov; M. V. Storozheva; M. S. Makarov (Российский офтальмологический журнал, 2023)
Purpose: to compare the effectiveness of conventional preserved amnion and amnion saturated with platelet-rich (PRP) plasma lysate for the treatment of persistent corneal erosions (PCE) after high-risk keratoplasty.Materials and methods. 40 patients with persistent corneal erosions after high-risk penetrating keratoplasty, followed up for 12 months, were divided into two clinical groups of 20 people each. The main group of patients, aged 34 to 84, received Flexamer amniotic membrane + PRP lysate, while the comparison group, aged 41 to 80, received Flexamer amniotic membrane only. Amniotic membrane coating was used in persistent corneal erosions of penetrating keratoplasty after unsuccessful conservative treatment. The amnion was sewn 2 mm from the limb with a continuous suture and covered with a soft contact lens. As a source of platelets, we used the blood of healthy volunteers, from which platelet-rich plasma with platelet concentration of over 1000 thousand/µl was taken, which was then frozen at -40 °C and defrosted at 0…4 °C to obtain PRP lysate. The criteria for evaluating the effectiveness of both groups were the times of epithelialization, the number of amniotic membrane coatings, and the number of preserved transplants at the end of the follow-up.Results. Lyophilized amniotic membrane saturated with autologous PRP lysate growth factors was shown to be biocompatible. It was found to be safe for the patients, to reduce the epithelialization time, to reduce the number of operations required to cover the PÑE with the amnion, and to increase the likelihood of successful transparent and translucent engraftment of a penetrating keratograft.Conclusion. The use of a lyophilized amniotic membrane enriched with growth factors of autologous PRP lysate is a promising method for the treatment of PCE of the penetrating corneal graft after high-risk keratoplasty.